GENETICS OF COMMON WHEAT (TRITICUM AESTIVUM L.) RESISTANCE TO LOOSE SMUT (USTILAGO TRITICI (PERS.) JENS.) (REVIEW) - V. V. Syukov; S. E. Porotkin (Вавиловский журнал генетики и селекции)
The authors summarize their own research and data from the literature to overview the current knowledge of the genetics of soft wheat resistance to loose smut. The inheritance and chromosomal location of 12 resistance genes are considered. A bank of donors of efficient genes for spring wheat resistance to the pest has been established.